2021
DOI: 10.1148/radiol.2020202708
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Chest CT for SARS-CoV-2 Infection in Individuals with or without COVID-19 Symptoms

Abstract: CT with structured CO-RADS scoring has good diagnostic performance for COVID-19 pneumonia in both symptomatic (AUC=0.89) and asymptomatic (AUC=0.70) individuals (P<0.001). • In symptomatic individuals (42% PCR+), CO-RADS ≥ 3 detected positive PCR with acceptable sensitivity (89%) and specificity (73%) resulting in PPV of 70%. • In asymptomatic individuals (5% PCR+), CO-RADS ≥ 3 detected SARS-CoV-2 infection with low sensitivity (45%) but high specificity (89%) and PPV of 18%.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 19 publications
8
91
0
13
Order By: Relevance
“…Risk of bias with respect to reference test was rated high in three studies ( 23 , 26 , 27 ) because repeated RT-PCR testing was not used in all patients with a negative initial RT-PCR result and persistent clinical suspicion of COVID-19. Risk of bias with respect to reference test was rated unclear in one study ( 21 ), because it was not clear whether all patients with an initial negative RT-PCR result and a persistent clinical suspicion of COVID-19 underwent repeated RT-PCR testing. In one study ( 20 ), there was potential risk of bias with regard to flow and timing, because the time interval between CT and RT-PCR testing was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Risk of bias with respect to reference test was rated high in three studies ( 23 , 26 , 27 ) because repeated RT-PCR testing was not used in all patients with a negative initial RT-PCR result and persistent clinical suspicion of COVID-19. Risk of bias with respect to reference test was rated unclear in one study ( 21 ), because it was not clear whether all patients with an initial negative RT-PCR result and a persistent clinical suspicion of COVID-19 underwent repeated RT-PCR testing. In one study ( 20 ), there was potential risk of bias with regard to flow and timing, because the time interval between CT and RT-PCR testing was not reported.…”
Section: Resultsmentioning
confidence: 99%
“… 15 In addition, two recently published studies investigating the diagnostic accuracy of CO-RADS in RT-PCR confirmed cohorts confirmed its good performance in symptomatic individuals, thereby further supporting its application for triage. 23,24 Moreover, the readers were not blinded to the presence of clinical diagnosis of COVID-19 in the included patients, which may have artificially increased the interobserver agreement of the two systems due to the introduced bias. This, however, is also representative of a real-life clinical scenario during an epidemiologically severe situation where high pretest prevalence of COVID-19 is estimated and supporting clinical information is almost always available to the reporting clinicians, which was the case in a recent study evaluating the agreement of the RSNA COVID-19 chest CT classification scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Another novel application of 3D printing technique is to assist management with the recent coronavirus disease 2019 (COVID-19) pandemic which results in a shortage of medical supplies, in particular, the personal protective equipment (PPE) [ 85 , 86 , 87 , 88 ], given the primary presentation of respiratory symptoms by COVID-19 [ 89 , 90 , 91 , 92 , 93 ], although it is also associated with cardiovascular disease [ 94 , 95 , 96 , 97 ]. 3D printing is playing an important role in providing medical devices including PPE when we are still fighting against the COVID-19 as shown in some reports documenting an overview of 3D printing applications and challenges in the COVID-19 [ 87 , 98 ].…”
Section: Clinical Applications Of 3d Printing In Cardiovascular DImentioning
confidence: 99%